Association between innovative dockless bicycle sharing programs and adopting cycling in commuting and non-commuting trips. (March 2019) - Jia, Yingnan; Fu, Hua
Abstract: As a city-level intervention for travel mode, dockless bicycle-sharing programs provide great opportunities to promote bicycle travel in both commuting and non-commuting trips. Our study is the first to quantitatively examine whether dockless bicycle-sharing programs promote changes in travel mode in commuting and non-commuting trips, and to examine the association between change in travel mode and potential correlates. In May 2017, a cross-sectional study with a retrospective assessment was conducted to investigate travel modes before and after the launch of dockless bicycle sharing. A total of 1180 respondents provided complete self-administered questionnaires. After the advent of dockless bicycle sharing, the proportion of cyclists significantly increased from 21.9% to 30.9% in commuting and from 22.1% to 33.6% in non-commuting trips. The potential correlates of adopting cycling included age, living area, access to a public transportation stop/station, surroundings and aesthetics along the bicycle lanes, social norms, and travel mode before the advent of dockless bicycle sharing programs. Furthermore, the potential correlates of adopting cycling in travel mode differed by purpose of trips.